Paket Informasi Arsitektur Rumah Gadang Khas Minangkabau - Rahmadhanty, Yani; Desriyeni, Desriyeni (Ilmu Informasi Perpustakaan dan Kearsipan, 2019)
AbstractÂ The writing of this paper aims to describe and provide knowledge about the architecture of the typical rumah gadang minangkabau house to the community, especially the current millennial generation. The method used in this paper is a descriptive method with a qualitative approach. A qualitative approach is to collect data directly by conducting observations, interviews and literature. Based on the discussion, it can be concluded that there are 5 stages in the process of packaging information packages for the Minangkabau Typical Rumah Gadang Â Architecture. The stages are, (1) identifying user needs. Identification is done to find out how much information needs are needed by users; (2) carry out the process of determining the topic of information to be discussed; (3) carry out information gathering conducted by observation, interviews and literature searches; (4) conduct data analysis and selection of information that has been obtained in accordance with the topic; (5) carry out the process of packaging information that presents covers, introductory words, table of contents, chapter sections and conclusions.Keywords: information packaging, rumah gadang architecture.